Weight-gain independent effect of mirtazapine on fasting plasma lipids in healthy men - Katharina Lechner; Sarah Heel; Manfred Uhr; Tatjana Dose; Florian Holsboer; Susanne Lucae; Ludwig Schaaf; Stephany Fulda; Stefan Kloiber; Johannes M. Hennings (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Treatment with mirtazapine, a widely prescribed antidepressant, has been linked to weight gain and dyslipidemia. Whether dyslipidemia occurs secondary to increased appetite due to antidepressant treatment, or due to direct pharmacological effects of mirtazapine is unknown. The aim of this analysis is to complement our previously published results of the effect of mirtazapine on metabolism and energy substrate partitioning from a proof-of-concept, open-label clinical study (ClinicalTrials.gov NCT00878540) in 12 healthy males (20–25 years). We report the effect of a seven-day administration of mirtazapine 30 mg per day on weight and lipid metabolism in healthy men under highly standardized conditions with respect to diet, physical activity and day-night-rhythm and under continuous clinical observation. After a 7-day administration of mirtazapine 30 mg, we observed a statistically significant increase in triglyceride levels (mean change + 4.4 mg/dl; 95% CI [– 11.4; 2.6]; p = 0.044) as well as TG/HDL-C ratio (mean change + 0.2; 95% CI [– 0.4; 0.1]; p = 0.019) and a decrease in HDL-cholesterol (mean change – 4.3 mg/dl; 95% CI [2.1; 6.5]; p = 0.004), LDL-cholesterol (mean change – 8.7 mg/dl; 95% CI [3.8; 13.5]; p = 0.008), total cholesterol (mean change – 12.3 mg/dl; 95% CI [5.4; 19.1]; p = 0.005), and non-HDL-C (mean change – 8.0 mg/dl; 95% CI [1.9; 14.0]; p = 0.023). Notably, weight (mean change – 0.6 kg; 95% CI [0.4; 0.8]; p = 0.002) and BMI (mean change – 0.2; 95% CI [0.1; 0.2]; p = 0.002) significantly decreased. No change in waist circumference (mean change – 0.4 cm; 95% CI [– 2.1; 2.9]; p = 0.838) or waist-to-hip-ratio (mean change 0.0; 95% CI [– 0.0; 0.0]; p = 0.814) was observed. This is the first study showing unfavorable changes in lipid metabolism under mirtazapine in healthy individuals despite highly standardized conditions including dietary restriction, and despite the observation of a decrease of weight. Our findings support the hypothesis that mirtazapine has direct pharmacological effects on lipid metabolism. ClinicalTrials.gov: NCT00878540.

Idiopathic REM sleep behavior disorder as a long-term predictor of neurodegenerative disorders - Stephany Fulda (EPMA Journal, 2011)